The effects of Vitamin D3 supplementation on Spermatogram and endocrine factors in asthenozoospermia infertile men: a randomized, triple blind, placebo-controlled clinical trial - Leila Maghsoumi-Norouzabad; Ahmad Zare Javid; Anahita Mansoori; Mohammadreza Dadfar; Amirarsalan Serajian (BMC, 2021)
Abstract Objective Evaluate the effects of vitamin D3 (VD3) on sperm parameters and endocrine markers in infertile men with asthenozoospermia. Materials and methods This randomized, triple-masking, placebo-controlled clinical trial conducted on 86 asthenozoospermia infertile men with serum 25 hydroxy vitamin D3 (25(OH)VD3) < 30 ng/ml in the infertility clinic of Ahvaz Jahad daneshgahi, Iran. Patients were randomly allocated to groups A and B, who received daily 4000 IU VD3 and matching placebo respectively for 3 months. Demographic data, dietary intake, physical activity, sun exposure, anthropometric indices, serum 25(OH)VD3, luteinizing hormone (LH), follicle-stimulating hormone (FSH), total testosterone (T), estradiol (E2),, sex hormone-binding globulin (SHBG), free androgen index (FAI = T/SHBG. 100), T/LH and T/E2 ratios, prolactin (PRO), parathyroid hormone (PTH), osteocalcin (OCN), phosphorus and sperm parameters were assessed. Results Three months VD3 supplementation with 4000 IU/day had no significant effects body weight, body mass index (BMI), waist circumference (WC), body fat (BF), serum, OCN, LH, FSH, T, E2, SHBG, PRO, T/E2 ratio, FAI, semen volume, sperm count and normal sperm morphology. It increases serum 25(OH)VD3, PTH and phosphorus and seminal and serum calcium, T/LH ratio and total and progressive sperm motility and decreased significantly compared to the baseline and placebo group. Conclusion VD3 supplementation may affect sperm motility in men with asthenozoospermia and serum 25(OH)VD3 < 30 ng/ml. Trial registration Iran Clinical Trials Registry, ID: IRCT20151128025274N4, registered on 28 March 2018, URL of trial registry record: https://www.irct.ir/trial/29983